Ectopic ampulla with cholangitis: A case report - Kiran Shankar; Vikas Pemmada; Parvesh Kumar Jain (International Journal of Gastrointestinal Intervention, 2024)
Congenital anomalies of the biliary tree are rare and present challenges for endoscopists performing interventions such as endoscopic retrograde cholangiopancreatography (ERCP). The reported incidence of ectopic biliary drainage ranges from 2% to 20%, and the condition is often associated with pancreatobiliary complications, including choledocholithiasis (56%), cholangitis (39%), and acute pancreatitis (18.2%). These developmental abnormalities originate during embryogenesis. Uncommon sites for the ampullary opening include the third or fourth part of the duodenum, the stomach, and the pancreatic duct. We report a rare case of ectopic ampulla opening into the pylorus, which presented with cholangitis and was successfully managed with a modified ERCP technique.